First-principles calculations of the spin-orbit scattering cross section of sp impurities in Mg - N. Papanikolaou; N. Stefanou; P.H. Dederichs; S. Geier; G. Bergmann (Physical Review Letters, 1992)
The spin-orbit scattering of 4sp and 5sp impurities in a Mg host is investigated theoretically by self-consistent local-density-functional theory. The calculated spin-orbit scattering cross sections sigmaSO agree with the available experimental results for low valent impurities. For higher valent impurities we predict a p resonance behavior. For Cu and Ag impurities our results point to errors of density-functional theory in estimating the d contribution to sigmaSO. In total a consistent interpretation of the trends is given.